Sosial Media Instagram Untuk Promosi Usaha Perjalanan Wisata di Banjar Puseh Batubulan Kangin Gianyar Bali - Bagus Made Sabda Nirmala; Made Liandana; Pande Putu Gede Putra Pertama (Indonesian Journal Publisher, 2021)
Currently, technology is a basic requirement if a business wants to develop. Technology is no longer just a substitute for a business. Without technological support, a business will find it difficult to develop and generate profits. Not only in business processes, the promotion or marketing of business also requires technology. In this case, social media is a technology-based sharing platform that can help MSME players market their products. one of them is this service partner, UMKM Bali Daily Trip & Tour, which markets tour tour products. Products marketed are mainly the Nusa Penida Day Tour, which is a day tour in Nusa Penida. The development and improvement of a Bali Daily Trip & Tour UMKM business is very dependent on the use of existing technology, especially promotion using social media. UMKM actors must be able to take advantage of social media as a gathering place for their potential customers. One of the popular social media is Instagram. Instagram is currently an efficient promotional tool to get consumers, especially the youth market, who like holidays with tourist destinations in Bali. This community service aims to provide counseling on the use of social media as a media for promotion of tour packages for MSMEs Bali Daily Trip & Tour in Banjar Puseh, Batubulan Kangin, Gianyar Regency, Bali. Based on the results of the service activities that have been carried out, the participants have been able to understand the Insight feature which functions to determine the effectiveness of posted content and partners have also been able to determine a good posting schedule so that it can streamline the marketing process through social media.